1999
DOI: 10.1093/bja/83.2.340
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Post-tetanic count and train-of-four responses during neuromuscular block produced by vecuronium and infusion of nicardipine

Abstract: We have examined onset and recovery of neuromuscular block produced by vecuronium using either post-tetanic count (PTC), or the first twitch of the train-of-four (TOF) (T1/T0) and TOF ratio (T4/T1) during continuous infusion of nicardipine. Sixty adult patients were allocated to one of four groups of 15 patients each: nicardipine-PTC, nicardipine-TOF, control-PTC and control-TOF. In the nicardipine-PTC and nicardipine-TOF groups, nicardipine 0.03 mg kg-1 was given before vecuronium 0.1 mg kg-1 and a continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The success rate for "all muscles" indicates the percentage of patients with MEP responses from all muscle recording sites is followed by a post-tetanic increase in twitch tension (i.e., post-tetanic fasciculation of transmission). The post-tetanic count after tetanic stimulation at 50 Hz for 5 s has therefore become an accepted technique to quantify the degree of intense neuromuscular bockade under the condition in which responses to single-twitch stimulation are no longer obtained [20][21][22]. Kakimoto et al [14] hypothesized that the application of tetanic stimulation to peripheral nerves prior to transcranial stimulation might augment the amplitudes of MEPs from the muscles that were innervated by the nerve subjected to the tetanic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate for "all muscles" indicates the percentage of patients with MEP responses from all muscle recording sites is followed by a post-tetanic increase in twitch tension (i.e., post-tetanic fasciculation of transmission). The post-tetanic count after tetanic stimulation at 50 Hz for 5 s has therefore become an accepted technique to quantify the degree of intense neuromuscular bockade under the condition in which responses to single-twitch stimulation are no longer obtained [20][21][22]. Kakimoto et al [14] hypothesized that the application of tetanic stimulation to peripheral nerves prior to transcranial stimulation might augment the amplitudes of MEPs from the muscles that were innervated by the nerve subjected to the tetanic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PTC and the TOF ratio represent the degree of neuromuscular blockade at the prejunctional region of the neuromuscular junction, and the T1/control is related to the depth of neuromuscular blockade in the postjunctional region [1]. As noted above, nicorandil speeds not only recovery of the T1/ control but also that of the TOF ratio.…”
Section: K Atp Channel Agonist (Nicorandil)mentioning
confidence: 81%
“…More than a decade ago many calcium channel blockers were reported to enhance the action of nondepolarizing neuromuscular relaxants [1][2][3]. Calcium channel blockers inhibit the release of acetylcholine at the neuromuscular junction and enhance the degree of neuromuscular blockade [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation